Prediction of post-contrast acute kidney injury by bedside ultrasonography - Mümin Murat Yazici; Enes Hamdioğlu; Nurullah Parça; Gürkan Altuntaş; Özcan Yavaşi; Özlem Bilir (BMC Emergency Medicine)
Abstract Background The incidence of contrast-induced acute kidney injury (CI-AKI) in the general population ranges from 0.6 to 2.3%, whereas for specific high-risk patients, the incidence can reach more than 30–40%. Ultrasound measurements of the development of CI-AKI after contrast-enhanced imaging for diagnosis in the emergency department (ED) have yet to be adequately studied. Accordingly, we aimed to evaluate the usefulness of Doppler ultrasound measurements for predicting CI-AKI in patients with normal renal function. Methods This prospective, observational, single-center study was conducted in the ED of a tertiary teaching and research hospital between 1 January and 1 July 2024. All patients who presented to the tertiary training and research hospital ED, who were admitted to the hospital with a decision to undergo contrast-enhanced tomography for diagnosis, and who did not meet any exclusion criteria were included in the study. Patients included in the study were evaluated by ultrasonographic measurements (interlobar renal artery peak systolic velocity (PSV), interlobar renal artery end-diastolic velocity (EDV), inferior vena cava (IVC) collapsibility index, and renal resistive index (RRI)). Results The postcontrast RRI cutoff values were calculated to predict CI-AKI. The area under the curve (AUC) for the postcontrast RRI was 0.914, and the cutoff value for the postcontrast RRI was 0.70 (≥), exhibiting 72.7% sensitivity and 95.6% specificity. Conclusion Postcontrast RRI ultrasound measurements performed after diagnostic contrast imaging in the ED show high specificity in predicting CI-AKI development. Postcontrast ultrasound measurements may predict CI-AKI development, allowing further measures to be taken. Further studies are needed to confirm these findings. Trial registration Clinical trial number: not applicable.